2006
DOI: 10.1021/ci600216h
|View full text |Cite
|
Sign up to set email alerts
|

Refinement and Use of the Approximate Similarity in QSAR Models for Benzodiazepine Receptor Ligands

Abstract: Several considerations for refining the approximate similarity measurements have been introduced in this paper: the use of topological invariants for the calculation of similarity indexes and the development of new similarity correction processes. The quality of the new similarity measurements obtained with the proposed methods has permitted the development of fast, cheap, and simple quantitative structure-activity relationship models for the prediction of biological activities of nonbenzodiazepine gamma-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…They employed those descriptors showing high correlations with the activity under study and different similarity measures weighted by optimal consensus factors. In previous works, ,, we have shown the usefulness of the approximate similarity (AS) concept to develop QSAR models. Approximate similarity is based on correcting constitutional similarities by means of distance or dissimilarity values corresponding to the nonisomorphic fragments extracted from matching processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They employed those descriptors showing high correlations with the activity under study and different similarity measures weighted by optimal consensus factors. In previous works, ,, we have shown the usefulness of the approximate similarity (AS) concept to develop QSAR models. Approximate similarity is based on correcting constitutional similarities by means of distance or dissimilarity values corresponding to the nonisomorphic fragments extracted from matching processes.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most employed similarity measurements is based on mapping fragments of a molecule into bits of a binary string (fingerprint). It has been shown that fingerprints provide a nonintuitive encoding of molecular size, shape, and global similarity. Other common similarity measurements are based on the isomorphism calculation (e.g., maximum common substructure), and recently, similarity measurements which employ distances between topological descriptors computed over 2D molecular representations have also been proposed. Through the use of these representations above, different similarity indices have been studied (e.g., Tanimoto, cosine, Raymond, etc.) to generate similarity values…”
Section: Introductionmentioning
confidence: 99%
“…This kind of proposal has also been used in other papers that use relative measurements and allow the generation of data representations that include a refinement that favors the development of other QSAR models.…”
Section: Methodsmentioning
confidence: 99%
“…No biological activity was reported for ancorinazole, but a series of synthetic indolo[3,2- a ]carbazoles have been predicted to block binding of benzodiazepine to the γ-aminobutyric acid A/benzodiazepine receptor. 13,14 Screening of these naturally occurring metabolites in such an assay system could identify new lead structures for the development of medicines to target neurological and psychiatric disorders.…”
mentioning
confidence: 99%